A simple and accurate analytical model of the Stark profile and its application to plasma characterization. (March 2018) - Díaz-Soriano, A.; Alcaraz-Pelegrina, J.M.; Sarsa, A.; Dimitrijević, M.S.; Yubero, C.
Highlights: This method fits the Stark profiles for the Hβ line based on the CS model to an analytical function in order to simplify the calculus of the theoretical profile, which is obtained from the convolution of different functions corresponding to the different phenomena. This method doesn't assume the Stark contribution like a Lorentzian function, since it is well known that this consideration is erroneous. The application of this method is very useful due to permit to obtain three values for plasmas, at the same time: the electron density, the Gaussian and the Lorentzian broadenings. Abstract: Optical Emission Spectroscopy techniques are among the most employed to perform the characterization of laboratory plasmas. The analysis of the obtained data is based on the convolution of three different types of profiles: Lorentzians, Gaussians and Starks. While analytic expressions are available for the first two types, the Stark profile has been traditionally obtained through theoretical calculations using different models. In this paper, we propose is a simple and accurate analytical function that can be employed as approximation of a Stark profile. The application of this new model may simplify the analysis of plasmas.